Challenges and Strategies in Post-Mohs Reconstructive Surgery - McAllister, Lauren; Thornton, James F. (Seminars in Plastic Surgery, 2024)
Facial reconstruction following Mohs excision presents many challenges. The unpredictable nature of Mohs surgery can yield surprising deficits that require far more extensive reconstructions than originally anticipated. It is up to the reconstructive surgeon to guide the patient through the shock of the excision, initial reconstruction, definitive reconstruction, and postoperative management. It is essential to approach a post-Mohs patient with the understanding that a rushed, same-day reconstruction carries a greater risk for the patient and the outcome than that of a delayed, planned reconstruction. Considering factors beyond the deficits, such as the patient's means, health literacy, and comorbidities, is essential to ensuring a methodical reconstruction with favorable results. Often, deficits will need to be temporized until the patient is optimized and the details of the reconstruction have been established. The specifics of the reconstruction are heavily influenced by the patient's desires, understanding, and ability to participate multistage operations. Once the best suited reconstruction is selected, reviewing expectations and the possible associated contingencies is crucial for patient satisfaction. Despite the surgeon's great effort in ensuring a satisfactory reconstruction, many patients will further benefit from close follow-up and postoperative scar management. The combination of patient optimization, meticulous surgical planning, and postoperative wound management enables the surgeon to obtain favorable outcomes, even in the most unpredictable reconstructions.
Keywords: post-Mohs reconstruction; late resections; patient optimization; BTM